Aplikasi Penjualan Tunai Berbasis Web Pada CV. Damar Abadi Pontianak Pontianak - Nurmalasari Nurmalasari; Falentina Lidya Mega (Jurnal Sistem Informasi Akuntansi, 2020)
CV. Damar Abadi Pontianak is a company engaged in the sale of building materials which is still not computerized. The problems faced by CV. Damar Abadi Pontianak especially in the sales department is recording data on sales of goods, recording sales transactions, and recording financial statements still using a manual system that is the writing system. By looking at the problems above, the writer will build a Web -based cash sales application on the CV. Damar Abadi Pontianak. In this Web -based cash sales application there are several processes that can be made which include the login process, the registration process, the process of inputting data items, the process of sales transactions and the process of sales reports. The method used is object-oriented using the Prototype method with system design analysis tools using UML, namely use cases, activity diagrams, sequence diagrams and class diagrams. While making this cash sales application, the authors use PHP, HTML software and for the database using MySQL. This Web -based cash sales application can help the process of recording sales transaction data automation and report generation that is well integrated.